The Anti-Gattopardo: Lionardo Vigo’s Protostasi sicula. Archaeology, History and Politics - Girardi, Giacomo (Spunti e Ricerche, 2021)
This article aims to introduce the figure of the Sicilian erudite, writer and politician Lionardo Vigo (1799–1879) with a specific focus on his book Protostasi sicula o genesi della civiltà. The volume could be seen as the cultural and literary manifesto of a large group of men, so widespread in Sicily, who fought against the Italian unification under the aegis of the House of Savoy. It is a militant text, inserted into the political climate of the time and supported the concrete need of the island to self-govern or at least to obtain a particular administrative consideration in the new State’s construction. The article argues that there is a huge difference between Vigo and the Prince of Salina: Salina had the acumen to understand that his own survival, together with that of his entire class, was linked to a compromise with the new political order, an aspect that Vigo, a real anti-gattopardo, firm on his position, failed to grasp.